2019
DOI: 10.3390/app9091818
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Application of the Aerodynamic Admittance Functions of a Double-Deck Truss Girder

Abstract: This paper presents the aerodynamic admittance functions (AAFs) of a double-deck truss girder (DDTG) under turbulent flows. The objective of the investigation is to identify AAFs using a segment model wind tunnel test. All of the wind tunnel tests were based on the force measurement method and conducted in a passive spire-generated turbulent flow. The segment model adopts a typical DDTG section and is tested in the service and construction stages under 0°, 3°, and 5° wind attack angles. Furthermore, a nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A large number of studies have shown that a sudden change in wind speed near the bridge pylon is unfavorable for driving stability [18], and countermeasures have been explored for improving the wind environment at the bridge deck and ensuring driving safety [19,20]. Wind barriers, as an effective countermeasure, have had increasing attention from scholars [21][22][23]. Alonso-Estebanez et al [24] numerically studied and compared the aerodynamic coefficients of a truck on an embankment both with and without the wind fences installed.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that a sudden change in wind speed near the bridge pylon is unfavorable for driving stability [18], and countermeasures have been explored for improving the wind environment at the bridge deck and ensuring driving safety [19,20]. Wind barriers, as an effective countermeasure, have had increasing attention from scholars [21][22][23]. Alonso-Estebanez et al [24] numerically studied and compared the aerodynamic coefficients of a truck on an embankment both with and without the wind fences installed.…”
Section: Introductionmentioning
confidence: 99%